Spectral near field data of LED systems for optical simulations - Rotscholl, Ingo (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2018)
This book presents, validates and applies a fast, accurate and general measurement and modeling technique to obtain spectral near field data of LED systems for optical simulations in order to address the steadily increasing requirements of modern high quality LED systems. It requires only a minimum of goniophotometric near field measurements and no time-consuming angularly resolved spectral measurements. The obtained results can be used directly in state-of-the-art ray tracers.